Manajemen Sistem Informasi Akademik (Siakad) Untuk Meningkatkan Pelayanan Kepada Mahasiswa - cepagung muharam (ASWAJA: Jurnal Pendidikan dan Keislaman, 2021)
The improvement of the era requires an university to provide services to their students by collaborating service techniques carried out with advances in information and communication technology that are growing and developing. One system that answers these challenges is a system called Siakad. In theory, Siakad is defined as an application based on information and communication technology that is supported by a network that is used in one campus environment with the aim of helping all campus residents in carrying out their academic activities. To examine further about Siakad, the author presents research on Siakad management carried out at the Islamic Education Program Study of STAI Baitul Arqom Al-Islami Ciparay Bandung. This study aims to find out what activities are carried out to obtain an overview of planning, organizing, implementing and evaluating/supervising Siakad in improving services to students. The research method carried out by the author is a qualitative method with descriptive narrative presentation techniques. The data processing techniques used in this study include: data collection, data reduction, data display and conclusion/verification. In addition, the findings in the field are juxtaposed with existing theories. Based on the results of observations made, it was found that the Siakad management in the PAI STAI Baitul Arqom Al-Islami Study Program was arranged in such a way by integrating all available resources in order to improve services to students. Based on these findings, the authors conclude that the things that need to be done in Siakad management include: Siakad planning stages include: determining policies related to system design, inventorying resources and determining goals to be achieved. The organizing stages include: determining responsibilities and work procedures, as well as determining the person in charge of the system as a whole, technical implementers and the system supervisory body. The implementation stages include: optimizing and synergizing the hardware, software and brainware involved in accordance with the sequence and working procedures of each of these devices. Finally, the evaluation/supervision phase involves the supervisory body which includes: analyzing the strengths and weaknesses of the system and gathering information related to feedback from users of Siakad benefits.